Cancer Prevention Beliefs and Diet Behaviors Among Females Diagnosed with Obesity-Related Cancers (FS13-06-19). (13th June 2019) - Lin, Annie; Finch, Laura; Stump, Tammy; Hoffman, Sara; Spring, Bonnie
Abstract: Objectives: Obesity-related cancers (e.g., breast, colorectal, and endometrial) account for 40% of all US cancer diagnoses and disproportionately affect females. More than half of Americans are unaware that excess adiposity is a modifiable risk factor for certain types of cancers, and many do not perform healthy diet behaviors. It is unclear whether these patterns also appear in survivors of obesity-related cancers, a disease that could potentially be prevented by a healthy diet and weight management. Thus, we examined beliefs about cancer prevention and diet behaviors among female survivors of obesity-related cancers. Methods: Adult female cancer survivors enrolled in cycles 1 or 2 of the Health Information National Trends Survey (HINTS) 5 were included in this study if they reported a diagnosis that met the Centers for Disease Control and Prevention definition for an obesity-related cancer ( n = 241). Data about 1) cancer history, 2) beliefs about cancer prevention, and 3) dietary behaviors (produce intake, eating out) were used in independent t-tests and Chi-square analyses. Due to the survey's complex sampling design, reported estimates were weighted and the jackknife replication method was used. Results: The sample had a mean age of 63.2 ± 2.8 years and a mean BMI of 27.3 ± 1.0 kg/m 2 . Ratings on a 4-point scale (1 = strongly agree, 4 = strongly disagree) revealed that participants viewed cancer as somewhat preventable. About half of the participants agreed that being overweight or obese (46%) and eating a healthy diet (53%) had 'a lot of' influence over cancer development. When examining diet behaviors, only a quarter of the participants reported eating ≥ 2 cups of fruit (21%) and vegetables (25%) daily. Overall, participants 'sometimes' to 'rarely' used caloric information from menus to make food decisions [mean score: 3.4 (SE 0.1); scale: 1 = always, 5 = never]. Conclusions: Female survivors of obesity-related cancers are somewhat aware that cancer can be prevented, but do not consistently perform behaviors that can reduce their risk of cancer reoccurrence. Collectively, the evidence suggests that clinicians should emphasize the importance of weight management for obesity-related cancers and provide diet strategies during consultations with this population. Funding Sources: All authors are being supported by the National Institutes of Health.